Fetal alleles predisposing to metabolically favorable adiposity are associated with higher birth weight. Issue 11 (13th December 2021) - Thompson, William D; Beaumont, Robin N; Kuang, Alan; Warrington, Nicole M; Ji, Yingjie; Tyrrell, Jessica; Wood, Andrew R; Scholtens, Denise M; Knight, Bridget A; Evans, David M; Lowe Jr, William L; Santorelli, Gillian; et al.
Abstract: Background: Higher birthweight is associated with higher adult body mass index (BMI). Alleles that predispose to greater adult adiposity might act in fetal life to increase fetal growth and birthweight. Whether there are fetal effects of recently identified adult metabolically favorable adiposity alleles on birthweight is unknown. Aim: We aimed to test the effect on birthweight of fetal genetic predisposition to higher metabolically favorable adult adiposity and compare that with the effect of fetal genetic predisposition to higher adult BMI. Methods: We used published genome wide association study data ( n  = upto 406 063) to estimate fetal effects on birthweight (adjusting for maternal genotype) of alleles known to raise metabolically favorable adult adiposity or BMI. We combined summary data across single nucleotide polymorphisms (SNPs) with random effects meta-analyses. We performed weighted linear regression of SNP-birthweight effects against SNP-adult adiposity effects to test for a dose-dependent association. Results: Fetal genetic predisposition to higher metabolically favorable adult adiposity and higher adult BMI were both associated with higher birthweight (3 g per effect allele (95% CI: 1–5) averaged over 14 SNPs; P  = 0.002; 0.5 g per effect allele (95% CI: 0–1) averaged over 76 SNPs; P  = 0.042, respectively). SNPs with greater effects on metabolically favorable adiposity tended to have greater effects on birthweight ( R 2  = 0.2912, P  = 0.027). There was no dose-dependent association for BMI ( R 2  = −0.0019, P  = 0.602). Conclusions: Fetal genetic predisposition to both higher adult metabolically favorable adiposity and BMI is associated with birthweight. Fetal effects of metabolically favorable adiposity-raising alleles on birthweight are modestly proportional to their effects on future adiposity, but those of BMI-raising alleles are not.